New generalizations of the zeta-function and the Tricomi funation - Virchenko, N.O.; Ponomarenko, A.M. (Reports of the National Academy of Sciences of Ukraine, 2016)
New generalizations of the zeta-function and the Tricomi function are presented, and their main properties are studied. These new generalizations are realized with help of the (τ, β)-generalized confluent hypergeometric function.